Student Work, Educational Achievement, and Later Employment: A Dynamic Approach - Stijn Baert; Brecht Neyt; Eddy Omey; Dieter Verhaest (Institute of Labor Economics (IZA), 2017)
This study examines the direct and indirect impact (via educational achievement) of student work during secondary education on later employment outcomes. To this end, we jointly model student work and later schooling and employment outcomes as a chain of discrete choices. To tackle their endogeneity, we correct for these outcomes' unobserved determinants. Using unique longitudinal Belgian data, we find that pupils who work during the summer holidays of secondary education are 15.3% more likely to have a job three months after leaving school. This premium to student work experience is higher when pupils also work during the academic year and diminishes for later employment outcomes. When decomposing this total effect, it turns out that the direct returns to student work overcompensate its non-positive indirect effect via tertiary education enrolment.
Keywords: I21; J24; C35; 330; education; transitions in youth; student employment; labour; dynamic treatment